Gene-specific sex effects on eosinophil infiltration in leishmaniasis. Issue 1 (December 2016) - Slapničková, Martina; Volkova, Valeriya; Čepičková, Marie; Kobets, Tatyana; Šíma, Matyáš; Svobodová, Milena; Demant, Peter; Lipoldová, Marie
Abstract Background Sex influences susceptibility to many infectious diseases, including some manifestations of leishmaniasis. The disease is caused by parasites that enter to the skin and can spread to the lymph nodes, spleen, liver, bone marrow, and sometimes lungs. Parasites induce host defenses including cell infiltration, leading to protective or ineffective inflammation. These responses are often influenced by host genotype and sex. We analyzed the role of sex in the impact of specific gene loci on eosinophil infiltration and its functional relevance. Methods We studied the genetic control of infiltration of eosinophils into the inguinal lymph nodes after 8 weeks ofLeishmania major infection using mouse strains BALB/c, STS, and recombinant congenic strains CcS-1, -3, -4, -5, -7, -9, -11, -12, -15, -16, -18, and -20, each of which contains a different random set of 12.5% genes from the parental "donor" strain STS and 87.5% genes from the "background" strain BALB/c. Numbers of eosinophils were counted in hematoxylin-eosin-stained sections of the inguinal lymph nodes under a light microscope. Parasite load was determined using PCR-ELISA. Results The lymph nodes of resistant STS and susceptible BALB/c mice contained very low and intermediate numbers of eosinophils, respectively. Unexpectedly, eosinophil infiltration in strain CcS-9 exceeded that in BALB/c and STS and was higher in males than in females. We searched for genes controlling high eosinophil infiltration in CcS-9 mice by linkage analysis in F2 hybrids between BALB/c and CcS-9 and detected four loci controlling eosinophil numbers.Lmr14 (chromosome 2) andLmr25 (chromosome 5) operate independently from other genes (main effects).Lmr14 functions only in males, the effect ofLmr25 is sex independent.Lmr15 (chromosome 11) andLmr26 (chromosome 9) operate in cooperation (non-additive interaction) with each other. This interaction was significant in males only, but sex-marker interaction was not significant. Eosinophil infiltration was positively correlated with parasite load in lymph nodes of F2 hybrids in males, but not in females. Conclusions We demonstrated a strong influence of sex on numbers of eosinophils in the lymph nodes afterL. major infection and present the first identification of sex-dependent autosomal loci controlling eosinophilic infiltration. The positive correlation between eosinophil infiltration and parasite load in males suggests that this sex-dependent eosinophilic infiltration reflects ineffective inflammation.